Dioxazolones and nitrile sulfites as electrolyte additives for lithium-ion batteries
Patent Information
- Application Number
- JP2023074014
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-07-25
- Filing Date
- 2023-04-28
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2038-08-31
AI Technical Summary
をもたらすことが知られている。
Smart Images

Figure 0007617972000024 
Figure 0007617972000025 
Figure 0007617972000026
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Patent Application No. 16 / 045,082, filed July 25, 2018, and U.S. Provisional Patent Application No. 62 / 687,594, filed June 20, 2018, the entire contents of which are incorporated herein by reference. The present disclosure relates to rechargeable battery systems, and more particularly to the chemistry of such systems, including effective electrolyte additives, for improving the performance of rechargeable lithium-ion battery systems. [Background technology]
[0002] Rechargeable batteries are essential components of energy storage systems for electric vehicles and grid storage (e.g., as backup power during power outages, as part of a microgrid, etc.). Lithium-ion based batteries are a common type of rechargeable battery.
[0003] Electrolyte additives have been shown to be effective and to improve the life and performance of lithium-ion based batteries. For example, in IEEE Transactions on Battery Science and Technology (2009) 23:1311-1323, five proprietary, undisclosed electrolyte additives were shown to extend cycle life compared to electrolyte systems containing no additives or only one additive. Other studies have focused on improving performance with electrolyte systems containing three or four additives, as described in IEEE Transactions on Battery Science and Technology (2009) 23:1311-1323. However, researchers typically do not understand the interactions between the various additives that allow them to work synergistically with the electrolyte and specific positive and negative electrodes. Thus, the identity of a particular system is often based on trial and error and cannot be predicted in advance.
[0004] Previous studies have not identified two-additive electrolyte systems that can be combined into lithium-ion battery systems to produce robust systems with sufficient properties for grid or automotive applications. As described in U.S. Patent No. 5,933,636, the two-additive systems studied (e.g., 2% VC+1% allyl methanesulfonate and 2% PES+1% TTSPi) typically performed less well than the three- and four-additive electrolyte systems. (See, e.g., Tables 1 and 2 of U.S. Patent No. 5,933,636.) U.S. Patent No. 5,933,636 discloses that a third compound, often tris(-trimethyl-silyl)-phosphate (TTSP) or tris(-trimethyl-silyl)-phosphite (TTSPi), was required at a concentration between 0.25 and 3 wt. % to produce a robust lithium-ion battery system. (See, e.g., paragraph 72 of U.S. Patent No. 5,933,636.) However, additives are expensive and difficult to include in lithium-ion batteries on a manufacturing scale, so simpler, more effective battery systems, including those with fewer additives, are needed.
[0005] To further the adoption of electric vehicles and grid energy storage applications, it is desirable to develop lithium-ion cell chemistries that offer longer life at high temperatures and high cell voltages without significantly increasing costs. The introduction of sacrificial electrolyte additives, on the order of a few weight percent, is a practical method to form a protective solid-electrolyte interphase (SEI) layer that limits electrolyte decomposition during cell storage and operation. In recent years, significant efforts have produced a number of such additives that can be used to improve cell performance for various applications. Examples include vinylene carbonate (VC), fluoroethylene carbonate (FEC), prop-1-ene-1,3-sultone (PES), ethylene sulfate (1,3,2-dioxathiolane-2,2-dioxide, DTD), and lithium difluorophosphate (LFO). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] US Patent Application Publication No. 2017 / 0025706 [Patent Document 2] US Patent Application Publication No. 2017 / 0025706 [Non-patent literature]
[0007] [Non-Patent Document 1] JC Burns et al., Journal of the Electrochemical Society, 160, A1451 (2013) Summary of the Invention [Problem to be solved by the invention]
[0008] The present application provides compositions for use as electrolyte additives in lithium ion battery systems. definition A "cell" or "battery cell" generally refers to an electrochemical cell, which is a device that can produce electrical energy from a chemical reaction or promote a chemical reaction through the introduction of electrical energy. A battery can contain one or more cells. "Rechargeable battery" generally refers to a type of electric battery that can be charged, discharged into a load, and recharged multiple times. In this disclosure, some examples are described based on Li-ion rechargeable batteries. Nevertheless, embodiments of the present invention are not limited to one type of rechargeable battery, but can be applied in conjunction with a variety of rechargeable battery technologies. [Means for solving the problem]
[0009] overview The present disclosure encompasses novel battery systems with less effective electrolyte additives that can be used in different energy storage applications, such as automotive and grid storage. More specifically, the present disclosure includes additive electrolyte systems that improve the performance and life of lithium ion batteries while reducing costs from other systems that rely on more or other additives. The present disclosure also provides methods for preparing the additives disclosed herein.
[0010] Certain embodiments described herein include a non-aqueous electrolyte for a lithium ion battery that includes at least one lithium salt, at least one non-aqueous solvent, and an additive component that includes at least one active additive. The at least one active additive is
[0011] (a) Formula (I): [ka]
[0012] wherein R is any aromatic substituent, any unsaturated aliphatic substituent, or any aliphatic substituent containing one or more fluorine atoms; or
[0013] (b) Formula (II): [ka]
[0014] wherein each of R, R', and R'' is hydrogen, an alkyl substituent, or an aromatic substituent; or
[0015] (c) Formula (III): [ka]
[0016] wherein R is any alkyl or aromatic substituent.
[0017] In certain further embodiments, the at least one active additive is in the range of 0.01 to 6 wt. % based on the total weight of the electrolyte solution. In other embodiments, the at least one active additive is in the range of 0.25 to 5 wt. % based on the total weight of the electrolyte solution. In other embodiments, the concentration of the at least one active additive is about 2 wt. %.
[0018] In other embodiments, the additive component comprises ethylene sulfate, lithium difluorophosphate, vinylene carbonate, and / or fluoroethylene carbonate. In further embodiments, the additive component comprises 3-phenyl-1,4,2-dioxazol-5-one.
[0019] In certain embodiments, at least one non-aqueous solvent is a carbonate solvent. In further embodiments, the carbonate solvent is ethylene carbonate or dimethyl carbonate. In yet other embodiments, the non-aqueous solvent comprises at least two non-aqueous solvents.
[0020] In another embodiment, a negative electrode; a positive electrode; and a lithium salt dissolved in at least one non-aqueous solvent;
[0021] (a) Formula (I): [ka]
[0022] wherein R is any aromatic substituent, any unsaturated aliphatic substituent, or any aliphatic substituent containing one or more fluorine atoms; or
[0023] (b) Formula (II): [ka]
[0024] wherein each of R, R', and R'' is hydrogen, an alkyl substituent, or an aromatic substituent; or
[0025] (c) Formula (III): [ka]
[0026] wherein R is any alkyl or aromatic substituent.
[0027] In certain further embodiments, the at least one active additive is in the range of 0.01 to 6 wt. % based on the total weight of the electrolyte solution. In other embodiments, the at least one active additive is in the range of 0.25 to 5 wt. % based on the total weight of the electrolyte solution. In other embodiments, the concentration of the at least one active additive is about 2 wt. %.
[0028] In other embodiments, the additive component comprises ethylene sulfate, lithium difluorophosphate, vinylene carbonate, and / or fluoroethylene carbonate. In further embodiments, the additive component comprises 3-phenyl-1,4,2-dioxazol-5-one.
[0029] In certain embodiments, at least one non-aqueous solvent is a carbonate solvent. In further embodiments, the carbonate solvent is ethylene carbonate or dimethyl carbonate. In yet other embodiments, the non-aqueous solvent comprises at least two non-aqueous solvents.
[0030] In another embodiment, the lithium ion battery has 95% retention of initial capacity after 200 cycles between 3.0 V and 4.3 V at a charge rate of C / 3 CCCV at 40° C. In a further embodiment, the lithium ion battery has 95% retention of initial capacity after 400 cycles between 3.0 V and 4.3 V at a charge rate of C / 3 CCCV at 40° C.
[0031] In another embodiment, an electric vehicle is provided having a rechargeable battery including a drive motor, a gearbox, electronics, and a battery system. The battery system includes a negative electrode; a positive electrode; and a lithium salt dissolved in at least one non-aqueous solvent.
[0032] (a) Formula (I): [ka]
[0033] wherein R is any aromatic substituent, any unsaturated aliphatic substituent, or any aliphatic substituent containing one or more fluorine atoms; or
[0034] (b) Formula (II): [ka]
[0035] wherein each of R, R', and R'' is hydrogen, an alkyl substituent, or an aromatic substituent; or
[0036] (c) Formula (III): [ka]
[0037] wherein R is any alkyl or aromatic substituent.
[0038] In certain further embodiments, the at least one active additive is in the range of 0.01 to 6 wt. % based on the total weight of the electrolyte solution. In other embodiments, the at least one active additive is in the range of 0.25 to 5 wt. % based on the total weight of the electrolyte solution. In other embodiments, the concentration of the at least one active additive is about 2 wt. %.
[0039] In other embodiments, the additive component comprises ethylene sulfate, lithium difluorophosphate, and / or vinylene carbonate. In further embodiments, the additive component comprises 3-phenyl-1,4,2-dioxazol-5-one.
[0040] In certain embodiments, at least one non-aqueous solvent is a carbonate solvent. In further embodiments, the carbonate solvent is ethylene carbonate or dimethyl carbonate. In yet other embodiments, the non-aqueous solvent comprises at least two non-aqueous solvents.
[0041] In another embodiment, the battery system has 95% retention of initial capacity after 200 cycles between 3.0 V and 4.3 V at a charge rate of C / 3 CCCV at 40° C. In a further embodiment, the battery system has 95% retention of initial capacity after 400 cycles between 3.0 V and 4.3 V at a charge rate of C / 3 CCCV at 40° C. [Brief description of the drawings]
[0042] [Figure 1] 1 is a schematic diagram of a vehicle equipped with a battery storage system.
[0043] [Diagram 2] FIG. 1 is a schematic diagram of an exemplary battery storage system.
[0044] [Diagram 3] FIG. 1 is a schematic diagram of a lithium ion battery cell system.
[0045] [Figure 4] 1 is a H NMR spectrum of 3-methyl-1,4,2-dioxazol-5-one (MDO) synthesized as described herein.
[0046] [Diagram 5] 1 is a 13C NMR spectrum of MDO synthesized as described herein.
[0047] [Figure 6] 1 is an FTIR spectrum of MDO synthesized as described herein.
[0048] [Figure 7] 1 is a H NMR spectrum of 3-phenyl-1,4,2-dioxazol-5-one (PDO) synthesized as described herein.
[0049] [Figure 8] 1 is a 13C NMR spectrum of PDO synthesized as described herein.
[0050] [Figure 9] 1 is an FTIR spectrum of PDO synthesized as described herein.
[0051] [Figure 10] 1 is a 1H NMR spectrum of benzonitrile sulfite (BS) synthesized as described herein.
[0052] [Figure 11] 13C NMR spectrum of BS synthesized as described herein.
[0053] [Figure 12]FTIR spectrum of BS synthesized as described herein.
[0054] [Figure 13] Figure 1 shows a graph of the differential capacity (dQ / dV) of the cells formed in NMC622B / graphite (left) and NMC532 / graphite (right) cells. The electrolyte solutions contained (a) MDO-, (b) PDO-, or (c) BS-based additive blends. "Control" cells were prepared without additive for comparison.
[0055] [Figure 14] (a) Change in cell volume due to gas generation during 4.3 V storage at 60 °C for 500 h, and (b) during cell formation to 4.3 V for NMC622B / graphite (left) and NMC532 / graphite (right) cells. The electrolyte solutions contained MDO, PDO, or BS-based additive blends.
[0056] [Figure 15] Figure 1 shows the cell voltages of NMC622 / graphite (left) and NMC532 / graphite (right) cells measured during 500 h of open circuit storage at 60 °C. The electrolyte solutions contained (a) MDO-, (b) PDO-, or (c) BS-based additive blends as indicated.
[0057] [Figure 16] (a) Rct after formation for 500 h storage at 60 °C and (b) Rct after cell formation to 4.3 V for NMC622 / graphite (left) and NMC532 / graphite (right) cells. The electrolyte solutions contained MDO-, PDO-, or BS-based additive blends, as indicated at the bottom of the figure.
[0058] [Figure 17](a–c) Normalized discharge capacity and (df) ΔV of NMC622 / graphite pouch cells cycled at 40 °C and C / 3 charge / discharge rates up to 4.3 V. Concentrations of electrolyte additives are as indicated.
[0059] [Figure 18] (a–c) Normalized discharge capacity and (df) ΔV of NMC532 / graphite pouch cells cycled at 40 °C and C / 3 charge / discharge rates to 4.3 V. Concentrations of electrolyte additives are as indicated.
[0060] [Figure 19] The PDO-containing cell shown in Figure 15b was charged to 4.3 V and stored for an additional 500 h at open circuit at 60 °C. The cell voltages of (a) NMC622 / graphite and (b) NMC532 / graphite cells were measured during 500 h of open circuit storage at 60 °C. The PDO-based additive blends are as shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0061] FIG. 1 illustrates basic components of a battery-powered electric vehicle (EV) 100. The EV 100 includes at least one drive motor (traction motor) 102A and / or 102B, at least one gearbox 104A and / or 104B coupled to the corresponding drive motor 102A and / or 102B, battery cells 106, and electronics 108. In general, the battery cells 106 power the electronics of the EV 100 and provide electricity to propel the EV 100 using the drive motor 102A and / or 102B. The EV 100 includes numerous other components not described herein but known to those skilled in the art. Although the EV 100 configuration of FIG. 1 is shown as having four wheels, different EVs may have fewer or more than four wheels. Additionally, different types of EVs 100, including motorcycles, aircraft, trucks, boats, and train engines, among other types of vehicles, may incorporate the inventive concepts described herein. Certain parts formed using embodiments of the present disclosure are It may be used in a vehicle 100.
[0062] FIG. 2 shows a schematic diagram of an exemplary energy storage system 200 showing various components. The energy storage system 200 typically includes a modular housing with at least a base 202 and four side walls 204 (only two are shown in the figure). The modular housing is generally electrically insulated from the contained battery cells 206. This can be done by physical separation, an electrical insulating layer, selection of an insulating material as the modular housing, any combination thereof, or otherwise. The base 202 may be an electrical insulating layer over a metal sheet, or a non-conductive / electrically insulating material such as polypropylene, polyurethane, polyvinyl chloride, another plastic, a non-conductive composite, or insulated carbon fiber. The side walls 204 may also include an insulating layer or be formed from a non-conductive or electrically insulating material such as polypropylene, polyurethane, polyvinyl chloride, another plastic, a non-conductive composite, or insulated carbon fiber. One or more interconnect layers 230 can be disposed over the battery cells 206, and the top plate 210 is disposed over the interconnect layer 230. The top plate 210 may be a single plate or may be formed from multiple plates.
[0063] The individual battery cells 106 and 206 are often lithium-ion battery cells having an electrolyte containing lithium ions and positive and negative electrodes. Figure 3 shows a schematic diagram of a lithium-ion cell 300. Lithium ions 350 are dispersed throughout an electrolyte 320 within a container 360. The container 360 may be part of the battery cell. The lithium ions 350 migrate between a positive electrode 330 and a negative electrode 340. A separator 370 separates the negative and positive electrodes. A circuit 310 connects the negative and positive electrodes.
[0064] The present disclosure provides novel electrolytes and battery systems for use in grid and electric vehicle applications such as those described above, as well as newly identified compounds and compositions for use in such systems. Certain embodiments described herein include a non-aqueous electrolyte for a lithium ion battery comprising at least one lithium salt, at least one non-aqueous solvent, and an additive component comprising at least one active additive. The at least one active additive comprises:
[0065] (a) Formula (I): [ka]
[0066] wherein R is any aromatic substituent, any unsaturated aliphatic substituent, or any aliphatic substituent containing one or more fluorine atoms; or
[0067] (b) Formula (II): [ka]
[0068] wherein each of R, R', and R'' is hydrogen, an alkyl substituent, or an aromatic substituent; or
[0069] (c) Formula (III): [ka]
[0070] wherein R is any alkyl or aromatic substituent.
[0071] Exemplary 3-aryl substituted 1,4,2-dioxazol-5-one compounds according to certain embodiments include those shown in Table 1. [Table 1] [ka]
[0072] Chemical structures of other exemplary additives for the electrolyte solutions discussed herein include the formulas shown above: 3-methyl-1,4,2-dioxazol-5-one (MDO) (Formula IV) and benzonitrile sulfite, 3-phenyl-1,3,2,4-dioxathiazole 2-oxide (BS) (Formula VI).
[0073] MDO, or 3-methyl-1,4,2-dioxazol-5-one, has shown the ability to passivate graphite anodes against exfoliation in the presence of propylene carbonate (PC), see, e.g., Chem. Mater., 2017, 29(18), pp7733-7739.
[0074] In certain further embodiments, the additives to the electrolyte solutions described herein are in the range of 0.01-6 wt.% based on the total weight of the electrolyte solution, while in other embodiments, the at least one active additive is in the range of 0.25-5 wt.%, 0.35-4.5 wt.%, 0.45-4 wt.%, 0.55-3.5 wt.%, 0.65-3 wt.%, 0.75-2.5 wt.%, 0.85-2 wt.%, 0.95-2 wt.%, 1.05-1.5 wt.%, 1-5 wt.%, 1-4 wt.%, 1-3 wt.%, 2-4 wt.%, 1-2 wt.%, 3-4 wt.%, 2-5 wt.%, or 2-4 wt.% based on the total weight of the electrolyte solution. In other embodiments, the concentration of the at least one effective additive is about 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.5%, 3% by weight. , 3.5%, 4% 4.5%, 5%, 5.5%, or 6% by weight.
[0075] The additive component may include combinations of additives described herein. Additionally, the additive component may include ethylene sulfate, lithium difluorophosphate, vinylene carbonate, fluoroethylene carbonate, and combinations thereof.
[0076] In certain embodiments, at least one non-aqueous solvent is a carbonate solvent. In further embodiments, the carbonate solvent is ethylene carbonate or dimethyl carbonate. In yet other embodiments, the non-aqueous solvent comprises at least two non-aqueous solvents.
[0077] In other embodiments, the battery systems described herein have 95% retention of initial capacity after 200 cycles between 3.0V and 4.3V at a charge rate of C / 3CCCV at 40° C. In further embodiments, the battery systems have 95% retention of initial capacity after 300 cycles between 3.0V and 4.3V at a charge rate of C / 3CCCV at 40° C. In further embodiments, the battery systems have 95% retention of initial capacity after 400 cycles between 3.0V and 4.3V at a charge rate of C / 3CCCV at 40° C.
[0078] LiNi 1-x-y Mn x Co y The cell formation, long-term cycling performance, and high-temperature storage behavior of MDO (Formula IV), 3-phenyl-1,4,2-dioxazol-5-one (PDO, Formula V) and BS (benzonitrile sulfite; alternatively 3-phenyl-1,3,2,4-dioxathiazole 2-oxide, Formula VI), as well as their binary blends, in O2(NMC) / graphite pouch cells were tested. Results reported by others strongly suggest that MDO acts primarily by passivating the graphite electrode. However, it is unclear whether these additives affect the positive electrode. Therefore, in the work described herein, each additive was also tested in binary additive mixtures with VC, DTD, and LFO, which are known to have beneficial effects at the positive electrode.
[0079] Differential capacity results show that MDO and PDO form a passive solid-electrolyte interphase layer on the graphite electrode during cell formation, whereas BS does not. PDO has been demonstrated to be a very promising new additive, especially when used as a binary blend with lithium difluorophosphate or ethylene sulfate. Pre-experimental setup
[0080] Although the battery system itself may be packaged differently according to the present disclosure, the experimental setup typically used a machined "sealed cell" to systematically evaluate the battery system using a common setup, including two additive electrolyte systems for use as positive and negative electrodes. All percentages referred to within this disclosure are percentages by weight unless otherwise specified. It will be understood by those skilled in the art that the type of additive used and the concentration employed will depend on the most desired and improved properties, as well as other components and designs used in the lithium ion battery being manufactured, and will be apparent from the present disclosure.
[0081] Additive synthesis MDO, PDO, and BS were synthesized using the routes shown below. [ka]
[0082] Reaction a) shows the synthesis of 3-methyl-1,4,2-dioxazol-5-one (MDO), reaction b) shows the synthesis of 3-phenyl-1,4,2-dioxazol-5-one (PDO) and reaction c) shows the synthesis of benzonitrile sulfite (BS).
[0083] All solvents and starting materials were used as received without further purification. Thionyl chloride (1M in CH2Cl2) and benzohydroxamic acid (98%) were purchased from Alfa Aesar. 1,1´-carbonyldiimidazole (CDI, ≥98%) and acetohydroxamic acid (95%) were purchased from Oakwood Chemical Inc. After preparation, the additives were characterized by nuclear magnetic resonance spectroscopy (NMR) and Fourier transform infrared spectroscopy (FTIR). Details of the synthesis and characterization results are presented below.
[0084] MDO and PDO were synthesized as follows. To a stirred solution of hydroxamic acid (5.00 g, 36.5 mmol, 1 equiv.) in dichloromethane (120 mL) was added 1,1´-carbonyldiimidazole (5.92 g, 36.5 mmol, 1 equiv.) in one portion. The mixture was stirred at room temperature for 30 min, quenched with 50 mL of 1N H2SO4, extracted with dichloromethane (3×40 mL), and dried over Na2SO4. The volatiles were removed under reduced pressure to give the 3-substituted 1,4,2-dioxazol-5-ones. The product (3-methyl-1,4,2-dioxazol-5-one) was recrystallized from diethyl ether using liquid nitrogen or from a 10:1 mixture of cyclohexane:acetone (3-phenyl-1,4,2-dioxazol-5-one). The structure of 3-methyl-1,4,2-dioxazol-5-one (MDO) is shown below. [ka]
[0085] The structure of 3-phenyl-1,4,2-dioxazol-5-one (PDO) is shown below. [ka]
[0086] Additional 3-substituted-1,4,2-dioxazol-5-ones including o-FDO, m-FDO, p-FDO, p-MODO, and TDO were also synthesized. These compounds were prepared by dissolving potassium carbonate (K2CO3, 3.32 g, 24.0 mmol, 2 equiv.) and hydroxylamine hydrochloride (HN2OH*HCl, 1.67 g, 24.0 mmol, 2 equiv.) in 40 mL of water (HO) and adding 60 mL of ethyl acetate to it. 12.0 mmol of the corresponding acyl chlorides (c-FDO: 2-fluorobenzoyl chloride; m-FDO: 3-fluorobenzoyl chloride; p-FDO, 4-fluorobenzoyl chloride; p-MODO: 4-methoxybenzoyl chloride; TDO: 2-thiophenecarbonyl chloride) were dissolved in 20 mL of ethyl acetate and added dropwise at 0 °C with constant stirring with a magnetic bar. The reaction was allowed to warm to room temperature and proceed with constant stirring for 16 hours. The aqueous layer was extracted with ethyl acetate (3×30 mL), dried over anhydrous sodium sulfate (Na2SO4), and the solvent was removed under reduced pressure. The residue from the previous step was added to 40 mL of dichloromethane, and 1,1´-carbonyldiimidazole (1.95 g, 12.0 mmol, 1 equiv) was added in one portion. The reaction was allowed to proceed for 30 minutes with constant stirring with a magnetic stir bar. The reaction was then quenched with 1M H2SO4 (25 mL), extracted with dichloromethane (3×25 mL), and then dried over anhydrous sodium sulfate. The solvent was removed under reduced pressure to give the product.
[0087] Benzonitrile sulfite (BS, 5-phenyl-1,3,2,4-dioxathiazole 2-oxide) was prepared as follows: To a solution of thionyl chloride (30 mL, 1 M, 30 mmol, 3 equiv.) was added benzohydroxamic acid (1.4 g, 10.0 mmol, 1 equiv.). The mixture was stirred at room temperature for 6 h. Excess thionyl chloride and solvent were removed under reduced pressure to give 5-phenyl-1,3,2,4-dioxathiazole 2-oxide (1.57 g, 80%). The product was recrystallized from diethyl ether using liquid nitrogen for purification. The structure of 5-phenyl-1,3,2,4-dioxathiazole 2-oxide is shown below. [ka]
[0088] Additive characterization After isolation and purification, the MDO, PDO, and BS additives synthesized as above were characterized by nuclear magnetic resonance spectroscopy (NMR) using a Bruker AV500 spectrometer controlled by ICON-NMR software. As shown in Figure 4, 1 MDO was characterized using H NMR (CDCl3, 500 MHz): 2.35 (s, 3H). As shown in Figure 5, 13 MDO was characterized using C NMR (CDCl, 125 MHz): 164.0, 154.2, 10.5. As shown in Figure 7, 1 PDO was characterized using H NMR (CDCl, 300 MHz): 7.83–7.89 (m, 2H), 7.61–7.69 (m, 1H), 7.50–7.59 (m, 2H). As shown in Figure 8, 13 PDO was characterized using C NMR (CDCl3, 125 MHz): 163.7, 154.0, 133.9, 129.6, 126.7, 120.3. As shown in Figure 10, 1 BS was characterized using H NMR (CDCl3, 500 MHz): 7.90-7.96 (m, 2H), 7.56-7.64 (m, 1H), 7.47-7.55 (m, 2H). As shown in Figure 11, 13 BS was characterized using C NMR (CDCl3, 125 MHz): 157.3, 133.1, 129.3, 128.2, 120.8. Chemical shifts are reported in ppm relative to the residual solvent peak.
[0089] The material was also measured by the MicroLab PC software, which was 4 cm -1The compounds were characterized by Fourier transform infrared spectroscopy (FTIR) using a Cary630 FTIR (Agilent Technologies) equipped with a germanium crystal attenuated total reflectance (ATR) accessory, measured at a resolution of 100 nm. The FTIR spectrum of 3-methyl-1,4,2-dioxazol-5-one (MDO) is shown in Figure 6, the spectrum of 3-phenyl-1,4,2-dioxazol-5-one (PDO) is shown in Figure 9, and the spectrum of BS is shown in Figure 12.
[0090] Lithium-ion cells Dry (no electrolyte), vacuum sealed LiNi 0.5 Mn 0.3 Co 0.2 O2(NMC532) / Graphite and LiNi 0.6 Mn 0.2 Co 0.2 O2 (NMC622) / graphite pouch cells (with capacities of ~220 mAh and ~230 mAh, respectively) were obtained from LiFun Technology (Tianyuan District, Zhuzhou, Hunan, China). The cells were cut under heat seal in an argon atmosphere glove box, dried at 80 °C under vacuum for 14 h, and then returned to the glove box for filling. All solutions were 1.2 mol L in a 3:7 by mass solvent blend of ethylene carbonate (EC) and dimethyl carbonate (DMC) obtained from BASF (<20 ppm HO). -1 LiPF6 (BASF, ≥99.9%) was used. Additives MDO (synthesized as above), PDO (synthesized as above), BS (synthesized as above), VC (BASF, ≥99.8%), DTD (Guangzhou Tinci Materials Tech.Co.Ltd., ≥98%), and LiPO2F2 (abbreviated as "LFO" ZnO, Shenzhen CapChem Tech.Co.Ltd., was added to this electrolyte solution either alone or as a binary blend at the mass percent indicated. The cell was filled with 1.0 ± 0.1 g of solution, sealed at -90 kPa gauge pressure using a small vacuum sealer (MSK-115A, MTI Corp.) and immediately held at 1.5 V at room temperature (21-25 °C) to prevent corrosion of the copper current collector during the subsequent wetting period of approximately 24 h. The cell was then loaded into a temperature-controlled box (40.0 ± 0.1 °C) and connected to a Maccor 4000 series automated testing system (Maccor Inc.). As gas formation was expected to occur during formation, the pouch cell was clamped using soft rubber (approximately 25 kPa gauge pressure), which has previously been observed to significantly improve the accuracy of the experiment.
[0091] Electrochemical Testing Formation of the SEI was performed by charging the cell to 4.3 V at C / 20, holding at 4.3 V for 1 h, discharging to 3.8 V at C / 20, then holding the cell at 3.8 V for 1 h. The cell was weighed in water before and after formation to allow the change in evacuated volume to be determined using Archimedes' principle. The pouch was then cut open in an argon atmosphere glove box to degas the cell and resealed using a small vacuum sealer. The cell was weighed again and electrochemical impedance spectroscopy (EIS) was measured at 10.0 ± 0.1 °C using a BioLogic VMP3 instrument (100 kHz to 10 mHz, ± 10 mV sine wave amplitude). After formation, the cell was stored or subjected to extended cycling.
[0092] For storage, the cell was maintained at 40±0.1°C while being cycled twice between 2.8 and 4.3 V, then held at 4.3 V for 24 h. The cell's temperature was then increased to 60±0.1°C and the cell voltage was recorded at open circuit for 500 h. After storage, the cell was again cycled twice and then charged to 3.8 V. EIS was then measured and the cell was again weighed in water to measure gas evolution during storage.
[0093] For extended cycling, the cells were maintained at 40±0.1°C and cycled by charging to 4.3 V at C / 3 and holding the voltage at 4.3 V until the charging current fell below C / 20. The cells were then discharged to 2.8 V at C / 3 and charged again. Slow charge-discharge cycling at C / 20 was performed every 50 cycles.
[0094] Density functional theory calculations Density functional theory (DFT) calculations were performed using Gaussian (G09.d01) as described in M.J. Frisch, G.W. Trucks, H.B. Schlegel, G.E. Cuseria, M.A. Robb, J.R. Cheeseman, et al., Gaussian09, Gaussian, Inc., Wallingford, CT, USA, (2009). Geometry optimization and normal mode analysis were performed using the M062X hybrid functional described in Y. Zhao and DG Truhlar, Theor. Chem. Acc., 120, 215-241 (2007); the IEFPCM-UFF implicit solvation model (ε=20) described in D.S.Haall, J.Self, and J.R.Dahn, J.Phys.Chem.C, 119, 22322-22330 (2015), J.Tomasi, B.Mennucci, and R.Cammi, Chem.Rev., 105, 2999-3094 (2005), and J.Tomasi, B.Mennucci, and E.Cances, J.Mol.Struct.THEOCHEM, 464, 211-226 (1999); and the 6-311++G(2df,2pd) basis set. The B3LYP hybrid functional generally provides a good balance of speed and accuracy, while the M062X double hybrid functional typically provides better accuracy for molecules with charge separation. To balance computational speed and accuracy, the polarizable continuum model (PCM) was chosen. The implicit solvation model does not take into account factors such as the solvation sheath structure and preferential solvation in binary solvents; There is an inherent loss of accuracy in the choice of standard electrode potentials, which were calculated according to the following reactions for (1) oxidation and (2) reduction of the molecular species M:
number
[0095] Full details of the calculation of electrode half-potentials from DFT calculated free energies of reactions, including the conversion of absolute to relative electrode potentials, are known in the art.
[0096] Results and Discussion During the first part of the first charging step, the potential of the positive electrode rises very slowly, while the potential of the negative electrode surface drops relatively quickly. As a result, during this "formation" step, the negative electrode SEI is generated, mainly by electrochemical reduction of EC and / or electrolyte additives at the graphite surface. Therefore, the graph of differential capacity vs. voltage (dQ / dV vs. V) for the first charging step shown in Figure 13 can be used to explore whether the additives in this experiment directly generate a negative SEI layer. The introduction of MDO into the cells increased the potential of the negative electrode by approximately 2.1 V in both cell types. cell This leads to a broad reduction feature starting at Li / Li (Figure 13). + Assuming that the potential of the Li / Li is approximately 3.5±0.1 V, this reduction is characterized by + It is estimated that the reduction begins at about 1.4 V vs. 2.6 V. Note that the reduction signature is very small and can only be seen in the cell containing 2% MDO (see inset). cell (About 0.9V vs Li / Li + ) an additional reduction feature is observed, the origin of which is unclear. However, calculations of the reduction potential of MDO using DFT reveal that this second feature, E 0 red,calc =0.67V vs Li / Li + Finally, the reduction of the EC cosolvent at 2.85 V was found to be close to the value of 2.85 V (Table 2). cell For comparison, Figure 13 includes the formation of a "control" cell prepared without additive. cellThe features have a larger area in the 1% MDO cell, indicating incomplete passivation of the graphite, but are very small in the 2% MDO cell. The results confirm previous observations reported by others that MDO passivates the graphite electrode surface.
[0097] The cells prepared with PDO show two distinct features in the differential capacity plot (Figure 13). The first reduction feature occurs at approximately 2.1 V for the NMC622 / graphite cell. cell (Approx. 1.4V vs. Li / Li + ), and about 2.0V for the NMC532 / graphite cell (see inset) (about 1.5V vs. Li / Li + The second characteristic is that both cell types start at about 2.35V cell (approximately 1.15V vs Li / Li + ). Like MDO, the latter has a DFT-calculated reduction potential of 1.18 V vs Li / Li + (Table 2). The reduction feature of EC is also weakly present in the PDO-containing cells, and its area is larger in the 1% PDO than in the 2% PDO cell. Furthermore, the area of the EC feature is much smaller in all PDO-containing cells compared to the additive-free cells. This indicates that PDO leads to the formation of a passive or at least partially passive SEI on the graphite electrode.
[0098] Finally, the cells prepared with BS also show two prominent features in the differential capacity graph (Figure 13). The areas of these features, which are directly proportional to the charge associated with the corresponding reduction, are significantly larger than those observed for the reduction of MDO and PDO. Also, the onset of these features is The potential ranges from 2.2 to 2.4 V between the two cell types and various additive blends. cell (Approx. 1.1 to 1.3V vs. Li / Li + ) and 2.4~2.6V cell (About 0.9 to 1.1 V vs. Li / Li + ) range. For BS, both features are consistent with the DFT-calculated reduction potential of 1.16 V vs. Li / Li+ (Table 2). In cells prepared with BS as an independent additive, the area of the reduction feature of EC is not significantly reduced. Thus, the differential capacity results indicate that the reduction of BS does indeed occur but does not produce a passivating SEI on the graphite surface.
[0099] [Table 2]
[0100] The standard reduction and oxidation potentials of the three additives are shown in Table 2. These were calculated with DFT using M06-2X / 6-311++g(2df,2pd) / IEF-PCM (ε=20). The experimental reduction potentials estimated from Figure 13 are provided for comparison.
[0101] The amount of gas produced after a complete formation cycle up to 4.3 V is summarized in Figure 14. While some gas production during formation is largely unavoidable, it is desirable to develop a solution chemistry that does not produce excessive gas. It is observed that the PDO-containing cell produced the least amount of gas, whereas the MDO-containing cell produced the most. As mentioned above, it is interesting that the passivation behavior of MDO at the negative electrode does not limit gas production. The cell with the control electrolyte produced about 1.2 mL of gas during formation due to EC reduction, while the cell with 2% MDO produced about 2 mL, suggesting that MDO is a major contributor to Li + +e - It is clear that MDO must react with DTD to produce gaseous products. Figure 14 shows that DTD mitigates gas production from MDO. Previous studies have shown that cells with 1% DTD or 2% DTD as the only additive (NMC111 / graphite cells) produce 0.8 mL and 1.0 mL of gas during formation. Other studies have also shown that significant gas is also produced during formation in NMC532 / graphite cells containing only DTD, and that this gas is primarily ethylene. Thus, it is believed that there is a synergistic effect in the behavior of MDO and DTD acting to limit gas production.
[0102] Following the formation and degassing protocols, the cells were assigned to two groups and subjected to either high temperature storage or extended cycling. In the former case, the terminal voltage was automatically measured every 6 hours for 500 hours while the cells were maintained at 60 °C (Figure 15). Some degree of self-discharge under such harsh conditions is inevitable, and this provides a practical opportunity to compare the performance of different cell chemistries over a relatively short timescale. Figure 15 shows the results of the cell cycles for MDO, PDO, and B. The results show that all of the VC and S exhibit poor storage behavior when used as independent additives. For all three additives, the introduction of DTD did not improve performance, whereas LFO offered some improvement over PDO and BS. During storage at high voltage and temperature, the generation of large amounts of gas is often a concern. Figure 14 shows that the PDO-containing cells produced the least gas in this experiment, whereas significant gassing occurred in the cells prepared with MDO. EIS was also measured to observe whether the impedance increased significantly during storage. However, the results summarized in Figure 16 indicate that the increase in impedance was not a significant concern for any of the cells tested in this experiment. Overall, the best storage performance was observed in the cells with VC as a co-additive, and the storage results suggest that PDO is the most promising of the three additives.
[0103] The remainder of the cells in this experiment were tested by extended cycling at 40°C and a C / 3 charge / discharge rate up to 4.3V. For the NMC622 / graphite cells, the MDO-containing cells performed less well than cells made with 2% VC, a common additive that provides a good "standard" comparison (Figure 17). This is the opposite of a report in S. Roeser, A. Lerchen, L. Ibing, X. Cao, J. Kasnatscheew, F. Glorius, M. Winter, and R. Wagner, Chem. Mater., 29, 7733-7739 (2017), who found that 2% MDO outperformed 2% VC or 2% FEC. This difference can be attributed to the very different electrolyte solution used in that experiment, 1M LiPF6 in PC, versus 1.2M LiPF6 in 25EC:5EMC:70DMC used in this study. Capacity retention for NMC622 / graphite cells prepared with 2% PDO (including binary blends) is comparable or better than 2% VC cells. Of these, 2% PDO + 1% DTD is the best performing blend, contrasting with the poorer storage behavior of this cell chemistry compared to 2% VC (Figure 17). Finally, cycling performance of BS in NMC622 / graphite cells (Figure 17) is comparable only to 2% VC cells for the 2% BS + 2% VC blend. Particularly troubling is the steep slope of ΔV vs. cycle number for BS-containing cells (ΔV is the difference between the average charge voltage and the average discharge voltage) (Figure 17). This is often a negative sign of the long-term performance of the cell. Thus, these results support previous observations that PDO is the most promising of the three additives developed in this experiment.
[0104] MDO-containing cells cycle fairly well in NMC532 / graphite cells, showing comparable capacity retention to the 2%VC cells at 1% MDO, 2% MDO + 1% DTD, and 2% MDO + 2% VC (Figure 18). However, all of the MDO-containing cells show a significant increase in ΔV versus cycle number. This indicates an increase in impedance, which is often an early indication that the cell will eventually show severe capacity fade and fail. Cells prepared with PDO as an independent additive show worse cycling performance than the 2%VC cells, both in terms of discharge capacity and ΔV (Figure 18). However, all of the PDO-based blends outperform the 2%VC in terms of capacity retention. 2%PDO + 1% DTD and 2%PDO + 1% LFO further show little increase in ΔV versus cycle number, indicating that both of these are potentially superior solution chemistries in NMC532 / graphite cells. Finally, all of the BS-containing cells fall below 2%VC for this cell type.
[0105] Finally, we investigated whether the storage performance of the PDO-containing cell improves or deteriorates over multiple charge storage cycles. Figure 19 shows the open circuit voltage of a PDO-containing cell that was already stored at 60°C for 500 hours (Figure 15b), then charged to an upper voltage limit of 4.3 V, and stored for another 500 hours. The results show that the voltage drop during this second storage period is significantly smaller compared to the first storage period. This finding indicates that PDO performs well in storage. This is important because it suggests that the SEI layer may require sufficient time for growth and maturation, but the long-term development of the additive-derived SEI layer is a complex area of research and is worthy of additional investigation to understand how the process can be modeled for accurate cell lifetime and performance development predictions.
[0106] Therefore, the cycling, gassing, and storage performance indicate that PDO is a promising new electrolyte additive, especially when used in combination with DTD and LFO co-additives. conclusion
[0107] This experiment characterizes the high-temperature storage and long-term cycling performance of lithium-ion NMC / graphite pouch cells prepared with a recently developed electrolyte additive, MDO, and two new additives, PDO and BS. Differential capacity versus voltage indicates that both MDO and PDO form a passive SEI layer on the graphite electrode surface during cell formation, whereas BS does not. The presence of multiple reduction peaks requires additional investigation for theoretical explanation, but the reduction features generally agree with DFT predictions. As individual additives, the PDO-containing cells perform best, but the VC-containing cells still outperform. The additives were also tested as binary blends with VC, DTD, and LFO. In long-term cycling tests, cells prepared with 2%PDO / 1%DTD and 2%PDO / 1%LFO additive blends outperform the VC-containing cells. However, the high-temperature storage behavior of the 2%PDO / 1%LFO is superior to that of the 2%PDO / 1%DTD blend. Those skilled in the art will appreciate that the compositions described herein may be further optimized, for example, by adjusting the ratios of the primary and secondary additives or by introducing ternary blends.
[0108] The above disclosure is not intended to limit the disclosure to the exact form or specific field of use disclosed. Therefore, it is contemplated that various alternative embodiments and / or modifications to the disclosure are possible in light of the disclosure, whether or not expressly described or implied herein. Although the embodiments of the disclosure have been described in this manner, those skilled in the art will recognize that changes can be made in form and details without departing from the scope of the disclosure. Therefore, the disclosure is limited only by the claims. References to additives in this specification refer to additives that are generally effective, unless otherwise specified herein.
[0109] In the above specification, the present disclosure has been described with reference to certain embodiments. However, as one skilled in the art will appreciate, the various embodiments disclosed herein may be modified or otherwise implemented in various ways without departing from the spirit and scope of the present disclosure. Thus, this description should be considered as illustrative and is for the purpose of teaching those skilled in the art how to make and use the various embodiments of the disclosed battery system. It should be understood that the forms of the disclosure shown and described herein should be construed as representative embodiments. Equivalent elements or materials may be substituted for those typically illustrated and described herein. Furthermore, certain features of the present disclosure may be utilized independently of the use of other features, all as will be apparent to those skilled in the art after having the benefit of this description of the present disclosure. The terms "including," "comprising," "incorporating," "consisting of," "having," "being," and the like, used to describe and claim the present disclosure, are intended to be construed in a non-exclusive manner, i.e., to allow for items, components, or elements not expressly described. References to the singular should also be construed to relate to the plural. References to "about" or "approximately" should be construed to mean plus or minus 10%. Similarly, references to any percentage of an additive should be construed to mean plus or minus 10%.
[0110] Furthermore, the various embodiments disclosed herein should be construed in an illustrative and explanatory sense, and should not be construed as limiting the present disclosure in any way. All coupling references (e.g., attached, affixed, coupled, connected, etc.) are used only to aid the reader in understanding the present disclosure, and do not form any limitations with respect to the position, orientation, or use of the systems and / or methods specifically disclosed herein. Thus, coupling references, if present, should be interpreted broadly. Moreover, such coupling references do not necessarily imply that two elements are directly connected to each other.
[0111] Additionally, all numerical terms, such as, but not limited to, "first," "second," "third," "primary," "secondary," "main," or other conventional terms and / or numerals, should be construed merely as identifiers to aid the reader in understanding the various elements, embodiments, variations, and / or modifications of the present disclosure, and in particular do not form any limitation with respect to the order or priority of any element, embodiment, variation, and / or modification relative to or over another element, embodiment, variation, and / or modification.
[0112] It will also be understood that one or more of the elements shown in the drawings / figures may be implemented in a more separate or integrated manner, or may be depicted as deleted or inoperative in certain cases, as may be useful depending on the particular application.
Claims
1. A lithium salt and a non-aqueous solvent; Formula (II): 【Chemistry 1】 An additive component comprising a 3-CRR'R''-substituted 1,4,2-dioxazol-5-one compound according to where R is an alkyl or aromatic substituent; an additive component, wherein R′ and R″ are each independently hydrogen, an alkyl substituent, or an aromatic substituent; Including, 11. A non-aqueous electrolyte for an energy storage device, wherein the additive component further comprises a composition selected from the group consisting of ethylene sulfate, lithium difluorophosphate, vinylene carbonate, fluoroethylene carbonate, and combinations thereof.
2. 2. The non-aqueous electrolyte of claim 1, wherein the concentration of the 3-CRR'R''-substituted 1,4,2-dioxazol-5-one compound is in the range of 0.01 to 6 wt %, based on the total weight of the non-aqueous electrolyte.
3. 2. The non-aqueous electrolyte of claim 1, wherein the concentration of the 3-CRR'R''-substituted 1,4,2-dioxazol-5-one compound is about 2 wt %, based on the total weight of the non-aqueous electrolyte.
4. The non-aqueous electrolyte of claim 1, wherein at least one of R, R', and R'' is an aromatic substituent.
5. The non-aqueous electrolyte of claim 1 , wherein the non-aqueous solvent comprises a carbonate solvent.
6. 6. The non-aqueous electrolyte of claim 5, wherein the carbonate solvent is selected from the group consisting of ethylene carbonate, dimethyl carbonate, and combinations thereof.
7. The non-aqueous electrolyte of claim 5 further comprising a second non-aqueous solvent.
8. Negative electrode; a positive electrode; and A non-aqueous electrolyte comprising a lithium salt, a non-aqueous solvent, and an additive component, the additive component comprising lithium difluorophosphate and a compound represented by formula (II): 【Chemistry 2】 wherein R, R', and R" are each independently hydrogen, an alkyl substituent, or an aromatic substituent; and a 3-CRR'R"-substituted 1,4,2-dioxazol-5-one compound according to the formula: An energy storage device comprising:
9. The energy storage device of claim 8, wherein at least one of R, R', and R'' is an aromatic substituent.
10. 9. The energy storage device of claim 8, wherein a concentration of the 3-CRR'R''-substituted 1,4,2-dioxazol-5-one compound is in the range of 0.01 to 6 wt %, based on the total weight of the non-aqueous electrolyte.
11. 9. The energy storage device of claim 8, wherein a concentration of the 3-CRR'R''-substituted 1,4,2-dioxazol-5-one compound is 2 wt. % based on the total weight of the non-aqueous electrolyte.
12. 10. The energy storage device of claim 8, wherein the additive component further comprises ethylene sulfate.
13. 9. The energy storage device of claim 8, wherein the additive component further comprises a composition selected from the group consisting of vinylene carbonate, fluoroethylene carbonate, and combinations thereof.
14. 10. The energy storage device of claim 8, wherein the non-aqueous solvent comprises a carbonate solvent.
15. 15. The energy storage device of claim 14, wherein the carbonate solvent is selected from the group consisting of ethylene carbonate, dimethyl carbonate, and combinations thereof.
16. 10. The energy storage device of claim 8, further comprising a second non-aqueous solvent.
17. 10. The energy storage device of claim 8, comprising 95% retention of initial capacity after 200 cycles between 3.0V and 4.3V at a charge rate of C / 3 CCCV at 40°C.
18. 10. The energy storage device of claim 8, comprising 95% retention of initial capacity after 400 cycles between 3.0V and 4.3V at a charge rate of C / 3 CCCV at 40°C.
19. Drive motor; Gearbox; Electronic equipment; and 1. An electric vehicle having a rechargeable battery comprising an energy storage device comprising a negative electrode, a positive electrode, and a non-aqueous electrolyte, The non-aqueous electrolyte comprises a lithium salt, a non-aqueous solvent, and Formula (II) : 【Chemistry 3】 wherein R, R', and R" are each independently hydrogen, an alkyl substituent, or an aromatic substituent; The energy storage device has a retention of 95% of its initial capacity after 200 cycles between 3.0V and 4.3V at a charge rate of C / 3 CCCV at 40° C.
20. 20. The electric vehicle of claim 19, wherein a concentration of the 3-CRR'R''-substituted 1,4,2-dioxazol-5-one compound is in the range of 0.01 to 6 wt %, based on the total weight of the non-aqueous electrolyte.
21. 20. The electric vehicle of claim 19, wherein a concentration of the 3-CRR'R''-substituted 1,4,2-dioxazol-5-one compound is 2 wt. %, based on the total weight of the non-aqueous electrolyte.
22. 20. The electric vehicle of claim 19, wherein the additive component further comprises ethylene sulfate.
23. 20. The electric vehicle of claim 19, wherein the additive component further comprises lithium difluorophosphate.
24. 20. The electric vehicle of claim 19, wherein the additive component further comprises a composition selected from the group consisting of vinylene carbonate, fluoroethylene carbonate, and combinations thereof.
25. 20. The electric vehicle of claim 19, wherein the non-aqueous solvent comprises a carbonate solvent.
26. 26. The electric vehicle of claim 25, wherein the carbonate solvent is selected from ethylene carbonate, dimethyl carbonate, and combinations thereof.
27. 20. The electric vehicle of claim 19, further comprising a second non-aqueous solvent.
28. 20. The electric vehicle of claim 19, wherein the energy storage device has retention of 95% of initial capacity after 400 cycles between 3.0V and 4.3V at a charge rate of C / 3 CCCV at 40°C.
Citation Information
Patent Citations
Electrolyte additives for lithium-ion battery systems
JP2020510278A
Electrolyte additives for lithium ion batteries
US20170025706A1